(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2016)
Despite numerous advantages of diatomaceous earth (DE), its use for direct mixing with grains to control stored-product insects remains limited because of some very serious obstacles and disadvantages. The main obstacles preventing a wider use of DEs for mixing with grain, such as health concerns, the reduction in bulk density, differences in insect species tolerance to the same DE formulation, the effects of grain moisture and temperature on the effectiveness against insects, the influence of various commodities on DE efficacy, the use of DEs in some other fields, and possible solutions for overcoming DE limitations during direct mixing with grains are described in this manuscript. The same attempts have been made to discover new ways of increasing significantly the effectiveness against insects when much lower concentrations are used for direct mixing with grains. If these newer enhanced formulations can respond to the existing limitations of diatomaceous earth, a wider utilization of diatomaceous earth may be expected to control stored-product insect pests.